Carbon-coated aluminum current collector suitable for positive electrode and capable of supplementing lithium and preparation method of carbon-coated aluminum current collector

By setting a grid-like active lithium layer and a carbon-coated layer on the aluminum foil of the lithium-ion battery to form a carbon-coated aluminum current collector, the problem of lithium consumption in the lithium-ion battery during the first charging process is solved, and the energy density and Coulomb efficiency of the battery are improved.

CN119725550AActive Publication Date: 2025-03-28JIANGYIN NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411591388.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-28
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

During the first charging process, existing lithium-ion batteries consume a large amount of lithium due to the formation of the SEI film, resulting in a decrease in the battery energy density and low Coulomb efficiency.

Method used

A carbon-coated aluminum current collector composed of aluminum foil, a grid-like active lithium layer and a carbon-coated layer is used, and a magnetron sputtering and conductive paste coating technology is arranged on the lithium-enhancing active area of ​​the aluminum foil to form a grid-like structure to supplement the consumed active lithium.

Benefits of technology

The Coulomb efficiency of the battery is improved, the loss of battery capacity and energy density is reduced, and the Coulomb efficiency of the first charging and discharging cycle of the battery is extended, ensuring that the positive end lithium ion loss is less, thereby improving the battery energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725550A_ABST
    Figure CN119725550A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of current collector preparation, in particular to a carbon-coated aluminum current collector suitable for a positive electrode and capable of supplementing lithium and a preparation method of the carbon-coated aluminum current collector. The carbon-coated aluminum current collector is composed of aluminum foil, a latticed active lithium layer and a carbon-coated layer, wherein the latticed active lithium layer and the carbon-coated layer are arranged on the aluminum foil. The method comprises the specific steps that S1, aluminum foil is fixed through a clamp, specifically, the regular quadrilateral net-shaped clamp is fixed to the upper portion of the aluminum foil, and the clamp and the aluminum foil are spaced and not overlapped; s2, arranging a latticed active lithium layer on the aluminum foil: sputtering a lithium target material onto the lithium supplementing active area of the aluminum foil obtained in S1 through magnetron sputtering, and obtaining the latticed active lithium layer on the aluminum foil; and S3, arranging a carbon-coated layer on the aluminum foil: under the protection of inert gas, coating conductive slurry in grids of the latticed active lithium layer to obtain the carbon-coated layer on the aluminum foil, and drying to obtain the carbon-coated aluminum current collector.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of current collector preparation, and in particular to a carbon-coated aluminum current collector suitable for positive electrode lithium supplementation and a preparation method thereof. Background Art

[0002] In recent years, with the rapid development of new energy vehicles, the new energy vehicle industry has continuously put forward higher requirements for the performance of lithium-ion batteries, among which the improvement of battery energy density is the most urgent. Under the existing lithium-ion battery system, in order to improve the battery energy density, the following aspects are mainly taken into consideration: on the one hand, the energy density can be improved by optimizing the battery structure, such as CTP technology, CTC technology, CTB technology, etc.; on the other hand, through the iteration of positive and negative electrode materials, such as the use of high-nickel ternary and high-voltage nickel-manganese materials for the positive electrode, and the use of high-capacity silicon and tin-based alloy negative electrodes for the negative electrode, the battery energy density can be greatly improved. In addition, lithium-ion battery lithium supplementation technology is also an important means to improve battery energy density. During the first charging process of lithium-ion batteries, the organic electrolyte will be reduced and decomposed on the surface of the negative electrode such as graphite to form a solid electrolyte interface (SEI) film, which permanently consumes a large amount of lithium from the positive electrode, resulting in a low coulomb efficiency (ICE) of the first cycle, thereby reducing the capacity and energy density of the lithium-ion battery. In addition, there are processes such as the deactivation of negative electrode material particles due to shedding and the irreversible deposition of lithium metal, which will consume the active lithium of the positive electrode and reduce the capacity and energy density of the battery.

[0003] Based on this, the present invention will propose a carbon-coated aluminum current collector suitable for replenishing lithium in the positive electrode, which can replenish the consumed active lithium in the positive electrode, thereby improving the energy density of the battery, which has important practical significance. Summary of the invention

[0004] The object of the present invention is to provide a carbon-coated aluminum current collector suitable for lithium supplementation in a positive electrode and a preparation method thereof, so as to solve the problems raised in the prior art.

[0005] To achieve the above object, the present invention provides the following technical solutions: A carbon-coated aluminum current collector suitable for positive electrode lithium supplementation, comprising an aluminum foil, a grid-shaped active lithium layer and a carbon-coated layer arranged on the aluminum foil; The thickness of the aluminum foil is 8-24 μm, and is specifically divided into two surfaces, A and B; The A surface is divided into three parts: A1, A2, and A3, and the B surface is divided into three parts: B1, B2, and B3. Figure 1 , Figure 2 As shown; A1, A3 and B1, B3 are blank areas for the tabs, and A2, B2 are active areas for lithium supplementation; The grid-like active lithium layer is obtained by sputtering a lithium target material and is disposed on the lithium supplement active areas A2 and B2 of the aluminum foil, and has a thickness of 1±0.2 μm; The carbon coating layer is obtained by coating with a conductive slurry, and is arranged in the grid of the grid-shaped active lithium layer, and has a thickness of 1±0.2 μm.

[0006] Furthermore, the grid-shaped active lithium layer and the carbon coating layer are arranged on at least one surface of the aluminum foil.

[0007] Furthermore, the carbon coating layer does not cover the grid-shaped active lithium layer, that is, the carbon coating layer and the grid-shaped active lithium layer are not in direct contact.

[0008] Furthermore, the method for preparing the carbon-coated aluminum current collector comprises the following steps: S1: Fix the aluminum foil with a clamp: Fix the regular quadrilateral mesh clamp on the top of the aluminum foil. The clamp and the aluminum foil should be spaced apart and not overlapped. The interval is 2-5 mm and they are ready for use. S2: Setting a grid-like active lithium layer on the aluminum foil: sputtering a lithium target onto the lithium replenishing active areas A2 and B2 of the spare aluminum foil obtained in S1 by magnetron sputtering, thereby obtaining a grid-like active lithium layer on the aluminum foil; S3: Setting a carbon coating layer on the aluminum foil: Under the protection of inert gas, a conductive slurry is coated in the grid of the grid-shaped active lithium layer to obtain a carbon coating layer on the aluminum foil. After drying, a carbon-coated aluminum current collector is obtained and stored in an oxygen-free environment. The structure is as follows: Figure 3 shown.

[0009] Furthermore, the dew point temperature of the preparation environment of the present invention is between -50 and 65°C.

[0010] Furthermore, the baffle of the regular quadrilateral mesh clamp has a side length of 2-16 mm and is fixed in the middle of the lithium replenishing active areas A2 and B2 of the aluminum foil, and is 1±0.2 cm away from the edge of the single-sided lithium replenishing active areas A2 and B2.

[0011] Furthermore, the parameters of the magnetron sputtering are: vacuum degree is 0.5×10 -2 ~5×10 -2 Pa, target spacing is 7~10cm, working gas is Ar, gas flow rate is 30~100sccm, pressure is 0.5~2Pa, sputtering power is 90~240W, substrate temperature is 25~50℃, and pre-sputtering time is 20~40min.

[0012] Furthermore, the conductive paste is composed of a mixture of the following components: by weight, 40-55% of a conductive agent, 10-25% of a modified binder, 0.5-2% of a wetting agent, and 25-40% of a solvent.

[0013] Furthermore, the preparation method of the modified binder is as follows: (1) adding sodium carboxymethyl cellulose to deionized water, stirring and mixing uniformly, and adding dilute hydrochloric acid to adjust the pH value to 5-6 to prepare a 0.1-1 g / L sodium carboxymethyl cellulose aqueous solution; (2) adding 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide to the sodium carboxymethyl cellulose aqueous solution, stirring and mixing uniformly, and then under nitrogen protection, stirring is maintained and 5-10 g / L of 6-amino-2-mercaptobenzothiazole ethanol solution is added dropwise thereto. After the addition is completed, stirring and reacting for 1-24 hours, the reaction is terminated, and finally freeze-dried to obtain modified sodium carboxymethyl cellulose; (3) stirring and mixing the modified sodium carboxymethyl cellulose, polyacrylic acid, deionized water and photoinitiator, irradiating with 350-370 nm ultraviolet light for 1-20 minutes, terminating the reaction, and removing the deionized water by drying to obtain a modified binder.

[0014] Furthermore, the mass ratio of the sodium carboxymethyl cellulose, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, N-hydroxysuccinimide and 6-amino-2-mercaptobenzothiazole is 1:(0.75-1):(0.45-0.5):(0.7-1).

[0015] Furthermore, the modified sodium carboxymethyl cellulose, polyacrylic acid, deionized water and photoinitiator are (0.1-0.3):5:2:(0.01-0.03).

[0016] The performance of the conductive paste on the current collector determines the conductivity of the electrode. If the conductivity is too low, it will affect the insertion and extraction of lithium, and thus affect the lithium replenishment effect. Therefore, improving the performance of the conductive paste is the key to promoting lithium replenishment. Binder modification is usually one of the most effective ways to provide conductive paste performance. Therefore, in the scheme, the carboxylic acid group of sodium carboxymethyl cellulose is activated by using 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide, and then 6-amino-2-mercaptobenzothiazole is added to combine with it to obtain modified sodium carboxymethyl cellulose with a mercapto group; finally, under ultraviolet light conditions, the modified sodium carboxymethyl cellulose and polyacrylic acid undergo a click reaction to prepare a modified binder. The modified binder can combine with the conductive agent to form a strong hydrogen bond, so that the conductive agent of the carbon-coated layer is more tightly combined, which plays a role in enhancing the conductivity of the current collector, thereby enhancing the lithium replenishment effect of the current collector.

[0017] Furthermore, the conductive agent includes but is not limited to one or a combination of conductive carbon black, conductive graphite, graphene, and carbon nanotubes.

[0018] Furthermore, the model of the wetting agent includes but is not limited to any one of BYK-ET-3000, BYK-ET-3002, and BYK-HY-1600.

[0019] Furthermore, the solvent includes but is not limited to a combination of one or more of N-methylpyrrolidone, N,N-dimethylformamide, dimethyl sulfoxide, xylene, and acetone.

[0020] Compared with the prior art, the present invention has the following beneficial effects: 1. The carbon-coated aluminum current collector prepared by the present invention improves the coulombic efficiency of the battery; 2. The carbon-coated aluminum current collector prepared by the present invention can replenish the active lithium consumed in the first charge and discharge, reducing the loss of battery capacity and energy density; 3. The carbon-coated aluminum current collector prepared by the present invention can replenish the active lithium consumed during the first charging process, reduce the irreversible capacity of the battery during the first charging, and thus improve the coulombic efficiency of the battery during the first charge and discharge cycle, ensuring that the lithium ion loss at the positive terminal is small, so that the battery capacity and energy density are less affected, and ultimately achieve the purpose of improving the battery energy density. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The surface of aluminum foil A is divided; Figure 2 The surface of aluminum foil B is divided; Figure 3 Schematic diagram of the structure of the carbon-coated aluminum current collector; in, Figure 3 In the grid, the oblique line part is the grid-shaped active lithium layer; the blank part is the carbon coating layer. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] In the following examples, all raw materials are from the following sources: sodium carboxymethyl cellulose with a purity of 99%, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride with a purity of 99%, CAS number: 25952-53-8, N-hydroxysuccinimide with a purity of 98%, CAS number: 6066-82-6, polyacrylic acid with a purity of 99%, CAS number 9007-20-9, item number: 9007-20-9, conductive carbon black with a purity of 99%, and N-methylpyrrolidone with a purity of 99%, which can be purchased from Hubei Yongkuo Technology Co., Ltd.; 6-Amino-2-mercaptobenzothiazole, purity 98%, CAS number: 7442-07-1, can be purchased from Shanghai Jinjinle Industrial Co., Ltd.; The photoinitiator model is 1173, with a purity of 99%, and can be purchased from Hubei Qifei Pharmaceutical Chemical Co., Ltd.; BYK-ET-3000 wetting agent can be purchased from Dongguan Huazhiyuan Chemical Co., Ltd.

[0024] Example 1: A method for preparing a carbon-coated aluminum current collector suitable for positive electrode lithium supplementation: S1: Fixing aluminum foil with a clamp: Fix a regular quadrilateral mesh clamp with a baffle side length of 2 mm on the top of the middle of the lithium replenishing active areas A2 and B2 of the aluminum foil with a thickness of 12 μm. The distance between the clamp and the edge of the single-sided lithium replenishing active areas A2 and B2 is 1 cm, and there is a 5 mm gap between the clamp and the aluminum foil. It is for standby use; S2: Setting a grid-like active lithium layer on the aluminum foil: Sputtering a lithium target onto the lithium replenishing active areas A2 and B2 of the aluminum foil obtained in S1 by magnetron sputtering, and obtaining a grid-like active lithium layer with a thickness of 1 μm on the aluminum foil; wherein, the magnetron sputtering parameters: the vacuum degree is 1×10 -2 Pa, target spacing is 7 cm, working gas is Ar, gas flow rate is 50 sccm, pressure is 1 Pa, sputtering power is 120 W, substrate temperature is 50 ° C, and pre-sputtering time is 20 min; S3: Setting a carbon coating layer on the aluminum foil: S31: Preparation of modified binder: (1) Add 10 parts of sodium carboxymethyl cellulose to deionized water, stir and mix evenly, and add dilute hydrochloric acid to adjust the pH value to 5.5 to prepare a 5 g / L sodium carboxymethyl cellulose aqueous solution; (2) Add 10 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 5 parts of N-hydroxysuccinimide to the sodium carboxymethyl cellulose aqueous solution, stir and mix evenly, and then, under nitrogen protection, keep stirring and drop 6 g / L 6-amino-2-mercaptobenzothiazole ethanol solution ( 8 parts of 6-amino-2-mercaptobenzothiazole are dissolved in anhydrous ethanol to prepare a 6 g / L 6-amino-2-mercaptobenzothiazole ethanol solution), after the addition is completed, the reaction is continued with stirring for 24 hours, the reaction is terminated, and finally, the modified sodium carboxymethyl cellulose is obtained by freeze-drying; (3) 2 parts of modified sodium carboxymethyl cellulose, 50 parts of polyacrylic acid, 20 parts of deionized water and 0.2 parts of a photoinitiator are stirred and mixed uniformly, and irradiated with 350 nm ultraviolet light for 15 minutes to terminate the reaction, and the deionized water is removed by drying to obtain a modified binder; S32: Prepare conductive paste: mix the following components evenly: by weight percentage, conductive carbon black 50%, modified binder 20%, BYK-ET-3000 wetting agent 1%, N-methylpyrrolidone 29%; S33: Under nitrogen protection, a conductive slurry is coated inside the grid of the grid-like active lithium layer to obtain a carbon coating layer with a thickness of 1 μm on the aluminum foil, ensuring that the carbon coating layer does not cover the grid-like active lithium layer. After drying, a carbon-coated aluminum current collector is obtained and stored in an oxygen-free environment.

[0025] Example 2: A method for preparing a carbon-coated aluminum current collector suitable for positive electrode lithium supplementation: S1: Fixing aluminum foil with a clamp: Fix a regular quadrilateral mesh clamp with a baffle side length of 5 mm on the top of the middle of the lithium replenishing active areas A2 and B2 of the aluminum foil with a thickness of 12 μm. The distance between the clamp and the edge of the single-sided lithium replenishing active areas A2 and B2 is 1 cm, and there is a 5 mm gap between the clamp and the aluminum foil. It is ready for use; S2: Setting a grid-like active lithium layer on the aluminum foil: Sputtering a lithium target onto the lithium replenishing active areas A2 and B2 of the aluminum foil obtained in S1 by magnetron sputtering, and obtaining a grid-like active lithium layer with a thickness of 1 μm on the aluminum foil; wherein, the magnetron sputtering parameters: the vacuum degree is 1×10 -2 Pa, target spacing is 7 cm, working gas is Ar, gas flow rate is 50 sccm, pressure is 1 Pa, sputtering power is 120 W, substrate temperature is 50 ° C, and pre-sputtering time is 20 min; S3: Setting a carbon coating layer on the aluminum foil: S31: Preparation of modified binder: (1) Add 10 parts of sodium carboxymethyl cellulose to deionized water, stir and mix evenly, and add dilute hydrochloric acid to adjust the pH value to 5.5 to prepare a 5 g / L sodium carboxymethyl cellulose aqueous solution; (2) Add 7.5 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 4.5 parts of N-hydroxysuccinimide to the sodium carboxymethyl cellulose aqueous solution, stir and mix evenly, and then under nitrogen protection, keep stirring and add 6 g / L 6-amino-2-mercaptobenzothiazole ethanol solution dropwise therein. (7 parts of 6-amino-2-mercaptobenzothiazole are dissolved in anhydrous ethanol to prepare a 6 g / L 6-amino-2-mercaptobenzothiazole ethanol solution). After the addition is completed, the reaction is continued to stir for 24 hours to terminate the reaction. Finally, the modified sodium carboxymethyl cellulose is obtained by freeze-drying. (3) 1 part of modified sodium carboxymethyl cellulose, 50 parts of polyacrylic acid, 20 parts of deionized water and 0.1 parts of a photoinitiator are stirred and mixed uniformly, and irradiated with 350 nm ultraviolet light for 15 minutes to terminate the reaction. The deionized water is removed by drying to obtain a modified binder. S32: Prepare conductive paste: mix the following components evenly: by weight percentage, conductive carbon black 50%, modified binder 20%, BYK-ET-3000 wetting agent 1%, N-methylpyrrolidone 29%; S33: Under nitrogen protection, a conductive slurry is coated inside the grid of the grid-like active lithium layer to obtain a carbon coating layer with a thickness of 1 μm on the aluminum foil, ensuring that the carbon coating layer does not cover the grid-like active lithium layer. After drying, a carbon-coated aluminum current collector is obtained and stored in an oxygen-free environment.

[0026] Example 3: A method for preparing a carbon-coated aluminum current collector suitable for positive electrode lithium supplementation: S1: Fixing aluminum foil with a clamp: Fix a regular quadrilateral mesh clamp with a baffle side length of 2 mm on the top of the middle of the lithium replenishing active areas A2 and B2 of the aluminum foil with a thickness of 12 μm. The distance between the clamp and the edge of the single-sided lithium replenishing active areas A2 and B2 is 1 cm, and there is a 5 mm gap between the clamp and the aluminum foil. It is for standby use; S2: Setting a grid-like active lithium layer on the aluminum foil: Sputtering a lithium target onto the lithium replenishing active areas A2 and B2 of the aluminum foil obtained in S1 by magnetron sputtering, and obtaining a grid-like active lithium layer with a thickness of 2 μm on the aluminum foil; wherein, the magnetron sputtering parameters: the vacuum degree is 1×10 -2 Pa, target spacing is 7 cm, working gas is Ar, gas flow rate is 50 sccm, pressure is 1 Pa, sputtering power is 120 W, substrate temperature is 50 ° C, and pre-sputtering time is 40 min; S3: Setting a carbon coating layer on the aluminum foil: S31: Preparation of modified binder: (1) Add 10 parts of sodium carboxymethyl cellulose to deionized water, stir and mix evenly, and add dilute hydrochloric acid to adjust the pH value to 5.5 to prepare a 5 g / L sodium carboxymethyl cellulose aqueous solution; (2) Add 10 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 5 parts of N-hydroxysuccinimide to the sodium carboxymethyl cellulose aqueous solution, stir and mix evenly, and then, under nitrogen protection, keep stirring and drop 6 g / L 6-amino-2-mercaptobenzothiazole ethanol solution ( 8 parts of 6-amino-2-mercaptobenzothiazole are dissolved in anhydrous ethanol to prepare a 6 g / L 6-amino-2-mercaptobenzothiazole ethanol solution), after the addition is completed, the reaction is continued with stirring for 24 hours, the reaction is terminated, and finally, the modified sodium carboxymethyl cellulose is obtained by freeze-drying; (3) 2 parts of modified sodium carboxymethyl cellulose, 50 parts of polyacrylic acid, 20 parts of deionized water and 0.2 parts of a photoinitiator are stirred and mixed uniformly, and irradiated with 350 nm ultraviolet light for 15 minutes to terminate the reaction, and the deionized water is removed by drying to obtain a modified binder; S32: Prepare conductive paste: mix the following components evenly: by weight percentage, conductive carbon black 50%, modified binder 20%, BYK-ET-3000 wetting agent 1%, N-methylpyrrolidone 29%; S33: Coating a conductive slurry in the grid of the grid-like active lithium layer to obtain a carbon coating layer with a thickness of 2 μm on the aluminum foil, ensuring that the carbon coating layer does not cover the grid-like active lithium layer, and obtaining a carbon-coated aluminum current collector after drying, which is stored in an oxygen-free environment.

[0027] Comparative Example 1: Comparative Example 1 is based on Example 1, with the following adjustments: no modified binder is used, polyacrylic acid is used instead, and other processes remain unchanged, specifically: A method for preparing a carbon-coated aluminum current collector suitable for lithium supplementation in the positive electrode: S1: Fixing aluminum foil with a clamp: Fix a regular quadrilateral mesh clamp with a baffle side length of 2 mm on the top of the middle of the lithium replenishing active areas A2 and B2 of the aluminum foil with a thickness of 12 μm. The distance between the clamp and the edge of the single-sided lithium replenishing active areas A2 and B2 is 1 cm, and there is a 5 mm gap between the clamp and the aluminum foil. It is for standby use; S2: Setting a grid-like active lithium layer on the aluminum foil: Sputtering a lithium target onto the lithium replenishing active areas A2 and B2 of the aluminum foil obtained in S1 by magnetron sputtering, and obtaining a grid-like active lithium layer with a thickness of 1 μm on the aluminum foil; wherein, the magnetron sputtering parameters: the vacuum degree is 1×10 -2 Pa, target spacing is 7 cm, working gas is Ar, gas flow rate is 50 sccm, pressure is 1 Pa, sputtering power is 120 W, substrate temperature is 50 ° C, and pre-sputtering time is 20 min; S3: Setting a carbon coating layer on the aluminum foil: S31: Prepare conductive paste: mix the following components evenly: by weight percentage, conductive carbon black 50%, polyacrylic acid 20%, BYK-ET-3000 type wetting agent 1%, N-methylpyrrolidone 29%; S32: Under nitrogen protection, a conductive slurry is coated inside the grid of the grid-like active lithium layer to obtain a carbon coating layer with a thickness of 1 μm on the aluminum foil, ensuring that the carbon coating layer does not cover the grid-like active lithium layer. After drying, a carbon-coated aluminum current collector is obtained and stored away from oxygen.

[0028] Comparative Example 2: Comparative Example 2 is based on Example 1, with the following adjustments: lithium is not sputtered on the aluminum foil, and other processes remain unchanged, specifically: A method for preparing a carbon-coated aluminum current collector suitable for lithium supplementation in the positive electrode: S1: Carbon coating layer is set on aluminum foil: S11: Preparation of modified binder: (1) Add 10 parts of sodium carboxymethyl cellulose to deionized water, stir and mix evenly, and add dilute hydrochloric acid to adjust the pH value to 5.5 to prepare a 5 g / L sodium carboxymethyl cellulose aqueous solution; (2) Add 10 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 5 parts of N-hydroxysuccinimide to the sodium carboxymethyl cellulose aqueous solution, stir and mix evenly, and then under nitrogen protection, keep stirring and drop 6 g / L 6-amino-2-mercaptobenzothiazole ethanol solution ( 8 parts of 6-amino-2-mercaptobenzothiazole are dissolved in anhydrous ethanol to prepare a 6 g / L 6-amino-2-mercaptobenzothiazole ethanol solution), after the addition is completed, the reaction is continued with stirring for 24 hours, the reaction is terminated, and finally, the modified sodium carboxymethyl cellulose is obtained by freeze-drying; (3) 2 parts of modified sodium carboxymethyl cellulose, 50 parts of polyacrylic acid, 20 parts of deionized water and 0.2 parts of a photoinitiator are stirred and mixed uniformly, and irradiated with 350 nm ultraviolet light for 15 minutes to terminate the reaction, and the deionized water is removed by drying to obtain a modified binder; S12: preparing conductive paste: uniformly mixing the following components: by weight percentage, conductive carbon black 50%, modified binder 20%, BYK-ET-3000 type wetting agent 1%, N-methylpyrrolidone 29%; S13: coating the conductive slurry on the aluminum foil to obtain a carbon coating layer with a thickness of 1 μm, and after drying, obtaining a carbon-coated aluminum current collector.

[0029] Performance test: (1) lithium iron phosphate material, conductive carbon black, carbon nanotubes, and polyvinylidene fluoride were mixed uniformly in a mass ratio of 95.6:1.3:0.8:2.3, and an appropriate amount of N-methylpyrrolidone was added to obtain a positive electrode slurry; (2) the positive electrode slurry was coated on the carbon-coated aluminum current collector prepared in the above example, and dried at 120°C to obtain a positive electrode plate; (3) graphite was used as a negative electrode plate and a porous PE film was used as a separator. The positive electrode plate, the negative electrode plate, and the separator were wound and assembled, and the tabs were welded. Then, they were encapsulated in an aluminum-plastic film, baked at 100°C to remove water, and non-aqueous electrolyte (commercial lithium hexafluorophosphate electrolyte) was injected. After sealing, formation, exhaust, and secondary sealing, a lithium-ion battery was prepared; (4) the lithium-ion battery was subjected to a battery performance test to test its coulombic efficiency and 1C capacity; the specific test results are shown in Table 1 below: Table 1

[0030] Result analysis: From the data in Table 1 above, it can be seen that the present invention significantly improves the coulombic efficiency and capacity of the battery by thickening the thickness of the grid-shaped active lithium layer and the carbon coating layer and lengthening the side length of the regular quadrilateral mesh clamp baffle; in addition, the modified binder in the present invention also affects the performance of the battery to a certain extent.

[0031] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A carbon-coated aluminum current collector suitable for positive electrode lithium supplementation, characterized in that: The carbon-coated aluminum current collector includes a grid-shaped active lithium layer and a carbon-coated layer; wherein the grid-shaped active lithium layer is obtained by sputtering a lithium target, is arranged on the lithium replenishing active area, and has a thickness of 1±0.2 μm; the carbon-coated layer is obtained by coating a conductive slurry, is arranged in the grid of the grid-shaped active lithium layer, and has a thickness of 1±0.2 μm; the carbon-coated layer does not cover the grid-shaped active lithium layer.

2. A carbon-coated aluminum current collector suitable for positive electrode lithium supplementation according to claim 1, characterized in that: The carbon-coated aluminum current collector further comprises an aluminum foil having a thickness of 8 to 24 μm; the grid-shaped active lithium layer and the carbon-coated layer are arranged on at least one surface of the aluminum foil.

3. A carbon-coated aluminum current collector suitable for positive electrode lithium supplementation according to claim 2, characterized in that: The aluminum foil is divided into two surfaces, A and B. The A surface is divided into three parts, A1, A2 and A3, and the B surface is divided into three parts, B1, B2 and B3. Among them, A1, A3 and B1, B3 are blank areas for the tabs, and A2 and B2 are active areas for lithium replenishment.

4. A method for preparing a carbon-coated aluminum current collector suitable for positive electrode lithium supplementation according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: Fix the aluminum foil with a clamp: Fix the regular quadrilateral mesh clamp on the top of the aluminum foil. The clamp and the aluminum foil should be spaced apart and not overlapped. The interval is 2-5 mm and they are ready for use. S2: Setting a grid-like active lithium layer on the aluminum foil: sputtering a lithium target onto the lithium replenishing active areas A2 and B2 of the aluminum foil obtained in S1 by magnetron sputtering, thereby obtaining a grid-like active lithium layer on the aluminum foil; S3: Setting a carbon coating layer on the aluminum foil: Under the protection of an inert gas, a conductive slurry is coated in the grid of the grid-shaped active lithium layer to obtain a carbon coating layer on the aluminum foil, and after drying, a carbon-coated aluminum current collector is obtained.

5. The method for preparing a carbon-coated aluminum current collector suitable for positive electrode lithium supplementation according to claim 4, characterized in that: The dew point temperature of the preparation environment of the present invention is between -50 and 65°C.

6. The method for preparing a carbon-coated aluminum current collector suitable for positive electrode lithium supplementation according to claim 4, characterized in that: The baffle of the regular quadrilateral mesh clamp has a side length of 2-16 mm and is fixed in the middle of the lithium replenishing active areas A2 and B2 of the aluminum foil, and is 1±0.2 cm away from the edge of the single-sided lithium replenishing active areas A2 and B2.

7. The method for preparing a carbon-coated aluminum current collector suitable for positive electrode lithium supplementation according to claim 4, characterized in that: The parameters of the magnetron sputtering are: vacuum degree is 0.5×10 -2 ~5×10 -2 Pa, target spacing is 7~10cm, working gas is Ar, gas flow rate is 30~100sccm, pressure is 0.5~2Pa, sputtering power is 90~240W, substrate temperature is 25~50℃, and pre-sputtering time is 20~40min.

8. The method for preparing a carbon-coated aluminum current collector suitable for positive electrode lithium supplementation according to claim 4, characterized in that: The conductive paste is composed of a mixture of the following components: by weight, 40-55% of a conductive agent, 10-25% of a modified binder, 0.5-2% of a wetting agent, and 25-40% of a solvent.

9. A method for preparing a carbon-coated aluminum current collector suitable for positive electrode lithium supplementation according to claim 8, characterized in that: The preparation method of the modified binder is as follows: (1) adding sodium carboxymethyl cellulose to deionized water, stirring and mixing uniformly, and adding dilute hydrochloric acid to adjust the pH value to 5-6, so as to prepare a 0.1-1 g / L sodium carboxymethyl cellulose aqueous solution; (2) adding 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide to the sodium carboxymethyl cellulose aqueous solution, stirring and mixing uniformly, and then dripping 5-10 g / L of 6-amino-2-mercaptobenzothiazole ethanol solution thereto under nitrogen protection, and continuing to stir and react for 1-24 hours after the dripping is completed, and then terminating the reaction, and finally freeze-drying to obtain modified sodium carboxymethyl cellulose; (3) stirring and mixing the modified sodium carboxymethyl cellulose, polyacrylic acid, deionized water and a photoinitiator, and irradiating the mixture with ultraviolet light of 350-370 nm for 1-20 minutes, and then terminating the reaction, and drying to obtain a modified binder; Among them, the mass ratio of sodium carboxymethyl cellulose, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, N-hydroxysuccinimide and 6-amino-2-mercaptobenzothiazole is 1:(0.75~1):(0.45~0.5):(0.7~1); modified sodium carboxymethyl cellulose, polyacrylic acid, deionized water and photoinitiator are (0.1~0.3):5:2:(0.01~0.03).

10. The method for preparing a carbon-coated aluminum current collector suitable for positive electrode lithium supplementation according to claim 8, characterized in that: The conductive agent includes one or a combination of conductive carbon black, conductive graphite, graphene, and carbon nanotubes; the model of the wetting agent includes any one of BYK-ET-3000, BYK-ET-3002, and BYK-HY-1600; the solvent includes one or a combination of N-methylpyrrolidone, N,N-dimethylformamide, dimethyl sulfoxide, xylene, and acetone.

Citation Information

Patent Citations

  • Carbon-coated aluminum foil containing lithium-supplementing additive and preparation method of carbon-coated aluminum foil

    CN110444728A

  • Lithium-supplementing current collector, preparation method and application thereof, negative pole piece and lithium ion battery

    CN111430723A

  • Modification method and application of silicon-based binder for negative electrode material of lithium ion battery

    CN112322223A

  • Lithium supplementing method of lithium ion battery

    CN112652738A

  • Carbon-coated current collector containing lithium supplementing coating, preparation method of carbon-coated current collector and lithium battery

    CN116169241A